Urgensi Penetapan Hakim Atas Permohonan Itsbat Nikah Sebagai Solusi Memperoleh Hak Identitas Hukum - Bachtiar, Moch. Yusuf; Daim, Nuryanto Ahmad (Universitas Wijaya Putra, 2023)
Marriage without a marriage certificate will have many consequences related to the various rights of the wife and the right to provide for the children born from her mother's womb, both material and immaterial that must be received in marriage, as well as rights to property owned while in the marriage. Marital life itself, as well as matters relating to rights relating to third parties. Such a marriage situation will experience problems when dealing with marriage documents as authentic proof of marriage. In this context the breakthrough of itsbat marriage law which was never found in Law Number 1 of 1974 was appreciated by the Compilation of Islamic Law / KHI precisely in the provisions of article 7 paragraphs (1), (2), (3) and technically formulated by the procedural guidelines chapter in PA/Society, that the rules for legalizing marriage/itsbat marriage, are made based on marriages held based on religion or not being recorded by the authorized VAT. Responding to the legal needs of Muslims regarding ownership of a marriage book, namely for married couples who are married religiously but whose legal certainty is doubtful in the eyes of the law. The itsbat marriage referred to in this study is the legalization of marriages by the Religious Courts according to their respective jurisdictions. The determination of itsbat of marriage by the Surabaya religious court is very urgent for legal certainty of husband and wife marriages that have not been registered at the Office of Religious Affairs (KUA).